Virus morphogenesis and viral entry as alternative targets for novel hepatitis C antivirals - Chapel, C; Zitzmann, N; Zoulim, F; Durantel, D (Future Medicine, 2006)
Hepatitis C virus (HCV) infection is a major public health concern. New antiviral drugs are required urgently to complement and improve the efficacy of current chemotherapies. Molecules specifically targeting viral enzymes are the most attractive in terms of drug development and are, therefore, the most studied. However, an antiviral strategy based uniquely on the utilization of this type of target is expected to encounter problems caused by the emergence of viral escape mutants as has already been widely described for HIV and hepatitis B virus. HCV morphogenesis and viral entry represent interesting, and yet unexploited, novel molecular targets. Inhibitors of morphogenesis have recently been identified and studied in different virus–cell systems. Some of these are currently being evaluated in clinical trials against HCV. This review focuses on HCV morphogenesis, viral entry and inhibition and presents clinical development perspectives of this new generation of antivirals.